An expanded search for simian foamy viruses (SFV) in Brazilian New World primates identifies novel SFV lineages and host age-related infections. Issue 1 (December 2015) - Muniz, Cláudia; Jia, Hongwei; Shankar, Anupama; Troncoso, Lian; Augusto, Anderson; Farias, Elisabete; Pissinatti, Alcides; Fedullo, Luiz; Santos, André; Soares, Marcelo; Switzer, William
Abstract Background While simian foamy viruses have co-evolved with their primate hosts for millennia, most scientific studies have focused on understanding infection in Old World primates with little knowledge available on the epidemiology and natural history of SFV infection in New World primates (NWPs). To better understand the geographic and species distribution and evolutionary history of SFV in NWPs we extend our previous studies in Brazil by screening 15 genera consisting of 29 NWP species (140 monkeys total), including five genera (Brachyteles, Cacajao, Callimico, Mico, andPithecia ) not previously analyzed. Monkey blood specimens were tested using a combination of both serology and PCR to more accurately estimate prevalence and investigate transmission patterns. Sequences were phylogenetically analyzed to infer SFV and host evolutionary histories. Results The overall serologic and molecular prevalences were 42.8 and 33.6 %, respectively, with a combined assay prevalence of 55.8 %. Discordant serology and PCR results were observed for 28.5 % of the samples, indicating that both methods are currently necessary for estimating NWP SFV prevalence. SFV prevalence in sexually mature NWPs with a positive result in any of the WB or PCR assays was 51/107 (47.7 %) compared to 20/33 (61 %) for immature animals. Epidemiological analyses revealed an increase in SFV prevalence with age in captiveCebus monkeys. Phylogenetic analysis identified novel SFVs inCacajao, Leontopithecus, andChiropotes species that had 6–37 % nucleotide divergence to other NWP SFV. Comparison of host and SFV phylogenies showed an overall cospeciation evolutionary history with rare ancient and contemporaneous host-switching forSaimiri andLeontopithecus andCebus xanthosternos, respectively. Conclusions We identified novel SFV in four neotropical monkey genera in Brazil and demonstrate that SFV prevalence increases with age inCebus monkeys. Importantly, our test results suggest that both molecular and serological screening are currently required to accurately determine infection with NWP SFV. Our study significantly expands knowledge of the epidemiology and natural history of NWP SFVs. The tools and information provided in our study will facilitate further investigation of SFV in NWPs and the potential for zoonotic infection with these viruses.